The effects of attitudes towards sustainability and market pressure on smallholders' readiness towards sustainability certification implementation - Ali, Fazlin; Mahmud, Muhammad Mu'az; Wong, Kelly Kai Seng; Sharifuddin, Juwaidah; Zainudin, Zanurul Huzaima; Jantan, Amer Hamzah; Muhd Kulal, Salamiah; Aman, Zaki; Mansor, Nur Hanani; Basaruddin, Nur Hana (Auricle Global Society of Education and Research, 2024)
This paper aims to investigate into the underexplored ground of market pressure and its relationship with attitudes toward sustainability certification among palm oil smallholders. Furthermore, it analyses the moderating role of market pressure in explaining the relationship between sustainability attitudes and the readiness to embark on sustainability certification among palm oil smallholders. Employing a quantitative research design, data were gathered from a randomized sample of 408 smallholders through the distribution of structured questionnaires. These data were subsequently subjected to rigorous analysis utilizing Partial Least Squares Structural Equation Modelling (PLS-SEM) to validate the research hypotheses. The research findings unveil the pivotal influence of market pressure on individuals' attitudes toward sustainability within the context of palm oil smallholders. Additionally, market pressure emerges as a significant catalyst in fostering readiness among smallholders to implement sustainability certification. The study thereby highlights the significance of market dynamics and their potential to influence smallholders' sustainability perspectives. This study extends the research understanding of the complex dynamics between sustainability attitudes, market pressure, and the readiness of smallholders to embark on the journey toward sustainability certification. By tapping into the awareness and knowledge of smallholders concerning market pressures, policymakers and industry stakeholderscan cultivate a more conducive environment for the adoption of sustainability practices within the palm oil industry. The research contributes significantly to the existing literature on attitudes toward sustainability, market pressure, and the readiness for implementing sustainability certification. Its findings emphasize the critical role played by market forces in shaping the sustainability landscape among palm oil smallholders, paving the way for informed policy interventions and industry practices.